(untitled) (Nexo Revista Científica, 2021)
The paper justifies the use of the "freight frame" as a method of organizing the movement of freight vehicle in large metropolitan areas on the example of Samara city district. The study presents the characteristics of the "freight frame" of major European cities, Kazan and Moscow. A comparative analysis of approaches to the organization of the movement of freight vehicle on the basis of the "freight frame" of Russian cities and cities of foreign countries is carried out. Based on the use of the Yandex.Traffic service, an analysis of the congestion of the main transport highways of the city was carried out, a map of the transport accessibility of the city of Samara was compiled with the calculation of the transport accessibility indices of its districts. To analyze the load of freight transport in the Samara region and the city of Samara, the intensity and composition of the traffic of freight transport on the major streets of the city were calculated using the NETVISION Traffic software and hardware complex, differentiated by months and day time. The result of the analysis allowed to identify the most significant problems of traffic management. On the basis of the used methods of freight traffic analysis, the necessity of implementing the "freight frame" model in the city of Samara was justified. A set of sequential measures is proposed to ensure the step-by-step formation of the freight frame model.